(untitled) (Physical Education, Health and Social Sciences, 2026)
A six-week research was conducted in order to regulate the impact of various stages of commercial phytogenic feed supplement, herbitol, on growing response, carcass value, and economic performance of broiler chickens. Cobb-500 chicks were then randomly selected and at the age of a hundred and eighty days in four treatments, which consisted of Control (no Herbitol), Group-A (2mL/L), Group-B (4mL/L) and Group-C (6mL/L) of Herbitol in drinking water. Three replicates were used in each group in the completely randomized design, and under the same management and vaccination guidelines, birds were reared. Growth performance data was gathered weekly and on the day of 42, samples of breast meat were subjected to standard AOAC (Association of Official Analytical Chemists) tests. ANOVA was used to perform the statistical analysis. The results obtained demonstrated that birds in Group A (2 mL/L Herbitol) recorded a notable (P<0.05) higher performance on various parameters. The final alive body mass (2210.4g) of this population was the highest, the water and feed consumption was greater, and feed ratio (1.82). There was also an improvement in the quality of the carcass as reflected in the high contents of moisture (64.91%), crude protein (19.71%), fat (2.40%), and ash (1.26) in the breast meat. Group A was the most economical in terms of net profit per bird (Rs.23.52) and lowest mortality rate (3%). Conversely, Group C (6mL/L) birds had poorer performance, increased mortality and financial loss, which means that there is possible metabolic pressure at high doses. All in all, Herbitol supplementation of 2 mL/L was effective in enhancing broilers growth, meat composition, survivability and profitability. The results also emphasize that dosage optimization of phytogenic additives should necessarily be applied to achieve optimal biological efficiency and economy in the production of poultry.